Constraining the solar neighbourhood age–metallicity relation from white dwarf–main sequence binaries. Issue 3 (29th May 2021) - Rebassa-Mansergas, A; Maldonado, J; Raddi, R; Knowles, A T; Torres, S; Hoskin, M; Cunningham, T; Hollands, M; Ren, J; Gänsicke, B T; Tremblay, P-E; Castro-Rodríguez, N; et al.
ABSTRACT: The age–metallicity relation (AMR) is a fundamental tool for constraining the chemical evolution of the Galactic disc. In this work, we analyse the observational properties of this relation using binary stars that have not interacted consisting of a white dwarf (WD) – from which we can derive the total age of the system – and a main sequence (MS) star – from which we can derive the metallicity as traced by the [Fe/H] abundances. Our sample consists of 46 widely separated, but unresolved spectroscopic binaries identified within the Sloan Digital Sky Survey, and 189 WD plus MS common proper motion pairs identified within the second data release of Gaia . This is currently the largest WD sample for which the metallicity of their progenitors have been determined. We find a flat AMR displaying a scatter of [Fe/H] abundances of approximately ±0.5 dex around the solar metallicity at all ages. This independently confirms the lack of correlation between age and metallicity in the solar neighbourhood that is found in previous studies focused on analysing single MS stars and open clusters.